2013
DOI: 10.1007/s10495-013-0962-z
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid differentially modulates apoptosis in skin melanoma and retinal pigment epithelial cells exposed to UV–VIS broadband radiation

Abstract: The signaling pathways via mTOR (mammalian target of rapamycin) and AMPK (AMP-activated protein kinase) play key roles in transcription, translation and carcinogenesis, and may be activated by light exposure. These pathways can be modulated by naturally occurring compounds, such as the triterpenoid, ursolic acid (UA). Previously, the transcription factors p53 and NF-κB, which transactivate mitochondrial apoptosis-related genes, were shown to be differentially modulated by UA. UA-modulated apoptosis, following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 57 publications
4
35
0
Order By: Relevance
“…On the other hand, ursolic acid significantly reduced the viability of cells even at the lowest (5 µM) concentration used. These results are in agreement with literature data showing that UA modulates mitochondrial redox activity and decreases mitochondrial membrane potential; this results in cell cycle phase arrest and consequently apoptosis of cells [11,12]. Moreover, UA treatment of cells may decrease the anti-apop-www.journals.viamedica.pl/ophthalmology_journal totic Bcl-2 protein level by its phosphorylation and degradation, but it does not affect pro-apoptotic Bcl-xS or Bax protein amounts.…”
Section: Oa and Ua Impact On Production Of Metalloproteinases (Mmp-2 supporting
confidence: 92%
“…On the other hand, ursolic acid significantly reduced the viability of cells even at the lowest (5 µM) concentration used. These results are in agreement with literature data showing that UA modulates mitochondrial redox activity and decreases mitochondrial membrane potential; this results in cell cycle phase arrest and consequently apoptosis of cells [11,12]. Moreover, UA treatment of cells may decrease the anti-apop-www.journals.viamedica.pl/ophthalmology_journal totic Bcl-2 protein level by its phosphorylation and degradation, but it does not affect pro-apoptotic Bcl-xS or Bax protein amounts.…”
Section: Oa and Ua Impact On Production Of Metalloproteinases (Mmp-2 supporting
confidence: 92%
“…Our observations could be supported by a recent study from Manna et al (2015), who showed that naringin inhibited gamma radiation-caused inflammation and oxidative DNA damage by controlling p53 and NF-κB signaling pathways in murine splenocytes (Manna et al, 2015). In another report, Lee et al (2014) showed that UV light exposure produced a loss of proliferation and an activation of NF-κB in the skin melanoma cells, while pre-treatment with UA significantly reduced the amount of phosphorylated NF-κB at 24 h post-exposure (Lee et al, 2014). These pieces of evidence support our hypothesis that the protective effects of UA against gamma radiation induced damage through the inhibition of oxidative stress cascade including ROS production, lipid peroxidation, DNA damage, and NF-kB activation.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that ursolic acid induced apoptosis of melanoma MM200, Mel-RM, Me4405, and A375 cell lines (Mahmoud et al, 2015). Moreover, it exhibited potential for protecting normal cells and sensitizing skin melanoma cells to UV irradiation (Lee et al, 2014). Apoptotic death of human malignant melanoma cells was also observed after incubation with oleanolic acid (A375 cells) (Cijo George et al, 2014) and betulinic acid (UISO-MEL-1 cells) (Tan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports on the cytotoxic activity of amyrin and lupeol against different human melanoma cells (Saleem et al, 2008; Chaabane et al, 2013). Chlorogenic acid has been shown to inhibit proliferation and act cytotoxically to melanoma cell line B16 (Lee et al, 2014). However, the cytotoxicity of the tested extracts against the UACC-903, UACC-647, and C32 lines is probably not associated with the presence of chlorogenic acid because the extract from roots that contained a high amount of this compound exhibited low or no cytotoxicity and did not induce apoptosis of the investigated cell lines.…”
Section: Discussionmentioning
confidence: 99%